Young workers' perception of brand image: main and moderating effects. Issue 3 (7th September 2015) - Myrden, Susan E.; Kelloway, Kevin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the relationship between an employer's brand image (i.e. symbolic and functional attributes) and job seekers' attraction to the firm among a sample of young workers. Design/methodology/approach – Job seekers completed a questionnaire regarding their knowledge of a particular firm, their perceived image of that firm, and their attraction toward that firm in terms of future employment. Moderated regression analyses were used to test the hypotheses of interest. Findings – Consistent with previous findings, both functional and symbolic attributes of the brand image were related to job seekers' attraction to the firm. In contrast to previous research, work experience moderated the effect of symbolic, but not functional, attributes such that these effects became stronger with more experience. Symbolic and functional attributes also interacted to predict job seekers' attraction to the firm. Research limitations/implications – The study is based on cross-sectional self-report data, which limits causal inference. Practical implications – Results suggest that young workers are particularly influenced by symbolic attributes of the organizations' brand image. Originality/value – This paper compares the role of symbolic and functional attributes in predicting young workers' attraction to the firm. Young workers are more influenced by symbolic attributes and these influences are stronger when individuals gain in work experience and when they perceive higher functional attributes.